Influence of the Design Parameters of a Screw Feeder Loading Mechanism on the Torque Value of the Drive Shaft - Vasylkiv, Vasyl; Radyk, Dmytro; Stashkiv, Mykola; Danylchenko, Larysa (Communications - Scientific Letters of the University of Zilina, 2023)
The processes of material capture and movement in a screw feeder are characterized by significant loads due to the pressure of a vertical load column, which creates additional resistance to the movement of the material, overcoming which leads to unproductive energy consumption. The paper aims to study the influence of the design parameters of the loading mechanism on the torque on the drive shaft of a screw feeder. The results of experimental studies and computer simulation of the design parameters of the loading mechanism relation (the length of the loading zone, the inclination angle of the rotating wall of the loading nozzle, its displacement value relative to the vertical axis of the auger operating part, and the height of the material in the loading nozzle), to the torque value on the drive shaft of the screw feeder for transportation of bulk cargo, are presented in this paper.
Keywords: screw feeder; bulk material; torque; loading mechanism; the length of the loading zone displacement of the loading nozzle